Assessing the Relationship between Monetary Stability and Financial Stability in CEMAC - (:unkn) unknown (My University, 2014)
The goal of this paper is to make an assessment of the correlation between monetary stabilitynamely price stability-and macro financial euphoria in the Economic and Monetary Community of Central Africa (CEMAC).Our methodological approach which combines econometrics, graphical and historical analyses, shows that the relationship between the selected indicators of macro financial exuberance and inflation is not obvious in all of CEMAC apart from the Central African Republic (CAF).Nonetheless, since we consider CAF is the only country in CEMAC to be constantly in a situation of political instability, we may assume that the positive correlation between euphoria and inflation in that country has little or nothing to do with monetary policy performances. This enables us to give an empirical justificationit is the originality of this researchthe persistent situation in liquidity excess and the credit rationing in CEMAC Zone. It even raises the question of whether lower inflation in CEMAC may be more associated to "Good Luck" than "Good Policy" hypothesis.
Keywords: African Research